Brief to the Senate Standing Committee on Legal and Constitutional Affairs Concerning Bill C-84 - The Inter-Church Committee for Refugees, . (Refuge: Canada’s Journal on Refugees, 1987)
Brief to the Senate Standing Committee on Legal and Constitutional Affairs concerning Bill C-84.